Risk Management In The Implementation of The Probolinggo - Banyuwangi Toll Road Construction Project Package - Anwar Amin, Farid; Patriadi, Andi; Sajiyo, Sajiyo (Green Publisher Indonesia, 2025)
The construction of the Probolinggo-Banyuwangi Toll Road Package 2 is a strategic project that plays a critical role in enhancing infrastructure connectivity in East Java. However, it faces significant risks arising from both internal and external factors. Internal challenges include limited availability of skilled manpower, inadequate heavy equipment, and poor project coordination, which hinder project efficiency. External challenges, such as fluctuating raw material prices, regulatory changes, and adverse weather conditions, further complicate the implementation of the project. These risks, if unmanaged, could result in delays, cost overruns, and compromised project quality. This study focuses on identifying key risk factors and developing effective mitigation strategies through qualitative and quantitative risk analysis. Priority risks, including material delivery delays, frequent design changes, and financial instability, were identified as critical to the project’s success. The findings underline the importance of proactive and structured risk management approaches, as guided by frameworks like ISO 31000 and AS/NZS 4360, which emphasize early risk identification, assessment, and mitigation during the planning phase. Furthermore, the research highlights the necessity of strong coordination among stakeholders, from government agencies to contractors and subcontractors, to mitigate risks collaboratively. Developing a risk-conscious organizational culture is crucial to ensuring project efficiency, not only in terms of cost but also in time and quality management. By implementing a systematic and integrated risk management framework, the Probolinggo-Banyuwangi Toll Road Package 2 project can serve as a model for managing risks effectively in large-scale construction projects. This study provides valuable insights for future infrastructure developments in Indonesia, emphasizing the importance of robust risk management practices for achieving project sustainability and success